The Utilization Of Folk Stories Based On Nyi Rambut Kasih's Local Wisdom As Literature Appreciation Teaching Materials In Elementary School - Meliani, Dhea (Didaktika, 2022)
Literary appreciation activities become a focus in the scope of Indonesian language learning in elementary schools and become the main goal of student achievement. In achieving this goal, learning tools are needed that are in accordance with the context of literary appreciation. Ideally, children's storybooks should be relevant to educational goals and cultural contexts. However, in fact, the provision of literature based on local wisdom is very limited and even lacks a proportional place, especially in elementary schools. The research objectives are (1) to describe the intrinsic elements and the function of moral values in the Nyi Rambut Kasih folklore. (2) developing teaching materials for Nyi Rambut Kasih folklore as a literary appreciation. The approach in this research is a qualitative approach. The methodology used is the content analysis method. Data analysis techniques were adapted from Miles and Huberman, namely data reduction, data display, and conclusions. While the data collection technique used is document analysis. The results showed that the folklore based on the local wisdom of Nyi Rambut Kasih can be used as teaching material for literary appreciation after studying the relevance, the content of the text, and the moral values contained.